Littoral Cell Angioma of the Spleen - Cui, X. W.; Ignee, A.; De Molo, C.; Schreiber-Dietrich, D.; Woenckhaus, M.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2013)
We report for the first time on the contrast-enhanced ultrasound (CEUS) features of littoral cell angioma of the spleen (LCA). A patient presented with the incidental finding of splenomegaly which was investigated using modern ultrasound techniques. B-mode technique revealed heterogenous splenic parenchyma and small hypoechoic lesions up to 30 mm in size. Colour Doppler imaging revealed no specific vascularity. CEUS showed arterial hyper- and hypoenhancement with pronounced demarcation in the late phase. In an assumption of malignancy the lesions were biopsied using ultrasound guidance. Histology showed LCA. In this case report we discuss LCA in the light of new ultrasound techniques and present a review of the literature.
Keywords: kontrastverstärkter Ultraschall; Milzraumforderungen; Littoralzellangiom; sonografisch gezielte Biopsie